Effect of age on the sex difference in Ironman triathlon performance - Piacentini, M. F.; Vleck, V.; Lepers, R. (Movement & Sport Sciences - Science & Motricité, 2019)
The aim of this study was to investigate the effect of age on the sex differences in (3.8 km) swim, (180 km) cycle, (42 km) run, and overall performance time at the 2018 Ironman triathlon World Championship. Sex differences in performance times were analysed for the top 10 male and female amateur triathletes of each 5 years age group between 18-24 years and 70-74 years. Independent of age, the averaged sex difference in swimming, cycling, running, and overall performance time was 14.0 ± 3.3%, 15.6 ± 3.1%, 15.3 ± 6.8% and 15.1 ± 3.6%, respectively. There was no significant change with age in the sex difference in performance for swimming. For both cycling and running, the sex difference in performance of the age groups whose athletes were older than 60 years were significantly greater than those of younger age groups. Such results suggest that, in Ironman triathletes, the increase in the sex difference in performance with advancing age is discipline dependent. Further examination of the (physiological and training load related) factors that are associated with the age-related decline in Ironman triathlon performance is required to understand why the sex difference in cycling and running performance increases with age.